Superparamagnetic Ni:SiO2-C nanocomposites films synthesized by a polymeric precursor method - Fonseca, F. C.; Jardim, R. F.; Escote, M. T.; Gouveia, P. S.; Leite, E. R.; Longo, Elson [UNESP] (Springer, 2011)
In this work, we report on the magnetic properties of nickel nanoparticles (NP) in a SiO2-C thin film matrix, prepared by a polymeric precursor method, with Ni content x in the 0-10 wt% range. Microstructural analyses of the films showed that the Ni NP are homogenously distributed in the SiO2-C matrix and have spherical shape with average diameter of similar to 10 nm. The magnetic properties reveal features of superparamagnetism with blocking temperatures T (B) similar to 10 K. The average diameter of the Ni NP, estimated from magnetization measurements, was found to be similar to 4 nm for the x = 3 wt% Ni sample, in excellent agreement with X-ray diffraction data. M versus H hysteresis loops indicated that the Ni NP are free from a surrounding oxide layer. We have also observed that coercivity (H (C)) develops appreciably below T (B), and follows the H (C) ae [1 - (T/T (B))(0.5)] relationship, a feature expected for randomly oriented and non-interacting nanoparticles. The extrapolation of H (C) to 0 K indicates that coercivity decreases with increasing x, suggesting that dipolar interactions may be relevant in films with x > 3 wt% Ni.
Keywords: Polymeric precursor method; Spin coating; Nickel nanoparticles; Superparamagnetism